Tropical agriculture : The development of production - Wrigley, Gordon (London: William Clowes and Sons Limited, 1961)
In Tropical Agriculture (first published in 1961 and now thoroughly revised and brought up to date), Gordon Wrigley - a noted British agronomist and development manager who for 25 years has worked and travelled extensively in Africa, Asia, Central and South America, Australia, and the Pacific islands - suggests the methods of attaining maximum agricultural production and soil fertility that may most effectively combat such a crisis. Dealing with factors as they affect tropical agriculture as a whole, rather than as they affect individual crops, he discusses such basic topics as crop ecology, culture, cattle, and general improvement in quality and quantity of production.
lje 12/07/17
Loans
Keywords: Tropical agriculture; Agricultural products - development; Development - production